ROLE OF SUBSTRATE ANTIHYPOXANTS IN CORRECTION OF ABNORMALITIES OF MYOELECTRICAL ACTIVITY OF GASTROINTESTINAL TRACT IN VICTIMS WITH SEVERE COMBINED TRAUMA - D. Sh. Sa’Dulaev; S. F. Bagnenko; P. A. Dubikaitis; I. G. Dzhusoev; A. V. Lapitskiy (Вестник хирургии имени И.И. Грекова)
The abnormalities of myoelectrical activity of gastrointestinal tract were detected in 80 victims with severe combined trauma. There were observed a decrease of total electrical activity and dyscoordination of electrical activity of sections of gastrointestinal tract. An application of substrate antihypoxants should normalize the indices of myoelectrical activity of gastrointestinal tract. This approach allowed elimination of imbalance of total power between superposed (the stomach, the duodenum) and other sections of gastrointestinal tract. This would remove dyscoordination contraction of the jejunum and the ileum.